Aktivitas Insektisida Ekstrak Kulit Batang Empat Famili Tumbuhan terhadap Ulat Krop Kubis Crocidolomia pavonana (F.) - Edy Syahputra; Djoko Prijono; Dadang Dadang; Syafrida Manuwoto; Latifah K Darusman (Universitas Gadjah Mada, 2004)
The objective of this study was to evaluate the insecticidal activity of bark extracts of 35 plant species belonging to four families (Clusiaceae, Lecythidaceae Meliaceae, and Sapindaceae) against the cabbage head caterpillar Crocidolomia pavonana. Extraction of the test plant materials were performed with maceration method using ethanol and methanol continued by counter-current distribution separation in ethylacetate and water. Bark extract preparation of each plant species was tested against C. pavonana larvae by leaf-feeding method at concentration of 0.25% and 0.5%. Second-instar C. pavonana larvae were fed extract-treated broccoli leaves for 48 hours, then were presented with untreated leaves until the surviving larvae reached the fourth-instar larvae. The number of dead larvae was recorded. The phytochemical test of bark extract of Calophyllum soulattri was done by qualitative method. The results showed that the bark extracts of C. soulattri (Clusiaceae), Barringtonia sarcostachys (Lecythidaceae), and Aglaia tomentosa (Meliaceae) exhibited good insecticidal activity. Methanol extract of C. soulattri barks possessed strong insecticidal activity against C. pavonana larvae with LC95 of 0.21%. This extract showed positive response in alkaloid and triterpenoid qualitative tests. Further studies are needed to identify insecticidal compounds in those active extracts.